Fast and low loss flexoelectro-optic liquid crystal phase modulator with a chiral nematic reflector - Wang, X; Fells, J; Yip, W; Ali, T; Lin, J; Welch, C; Mehl, G; Booth, M; Wilkinson, T; Morris, S; Elston, S (Nature, 2019)
In this paper, we demonstrate a flexoelectro-optic liquid crystal phase-only device that uses a chiral nematic reflector to achieve full 2 phase modulation. This configuration is found to be very tolerant to imperfections in the chiral nematic reflector provided that the flexoelectro-optic LC layer fulfils the half-wave condition. Encouragingly, the modulation in the phase, which operates at kHz frame rates, is also accompanied by low amplitude modulation. The configuration demonstrated herein is particularly promising for the development of next-generation liquid crystal on silicon spatial light modulators.